1989
DOI: 10.1002/ijc.2910440204
|View full text |Cite
|
Sign up to set email alerts
|

Serologic mapping and biochemical characterization of the carcinoembryonic antigen epitopes using fourteen distinct monoclonal antibodies

Abstract: A series of 14 monoclonal anti-carcinoembryonic antigen (CEA, Mr 180,000) antibodies (MAbs) that show a strong degree of selective reactivity for human colon carcinomas versus normal adult tissues were used to construct a serological map of the CEA molecule. The MAbs were generated using extracts of colon carcinomas as immunogen and are thus given a COL designation. None of the 14 COL-MAbs tested were reactive with purified non-specific cross-reacting antigen (NCA, Mr 55,000) from normal lung, although some sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The epitope recognized by MAb COG1 is resistant to periodate and neuraminidase, sensitive to pepsin, and partially resistant to heat, reduction alkylation, and pronase digestion (15). These data, and the reactivity of COL1 with deglycosylated CEA (15), suggest that COL1 reacts with a peptide determinant on CEA.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The epitope recognized by MAb COG1 is resistant to periodate and neuraminidase, sensitive to pepsin, and partially resistant to heat, reduction alkylation, and pronase digestion (15). These data, and the reactivity of COL1 with deglycosylated CEA (15), suggest that COL1 reacts with a peptide determinant on CEA.…”
Section: Discussionmentioning
confidence: 87%
“…Previous reports have shown that MAb COLl reacts with NCA-2 and NFA-2, although both of these antigens had a much lower affinity for COLl than CEA (15). Since NCA-2 is present in meconium and NFA-2 is found in normal adult feces, this crossreactivity should not present a problem in applying COL1 in the differential diagnosis of colon neoplasms (9,ll).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…COL-1 (IgG,), COL-4 (IgG,), and COL-12 (IgG,,) were purified from ascites fluid by ammonium sulphate precipitation and ionexchange chromatography (Colcher et al, 1984). In a previous study (Kuroki et al, 1989), it was shown that COL-1, COL-4, and COL-12 all recognize separate and distinct epitopes on the CEA molecule. The description of MAb D612 has been published (Muraro et al, 1989).…”
Section: Ma Bsmentioning
confidence: 98%
“…The mAb COL-1, an IgG2a, has a high affinity for CEA and has no detectable reactivity to granulocytes or to the CEA-related Ags NCA-1 and normal fecal Ag-1 (28). Murine COL-1 (mCOL-1) reacts with biopsies of colon and gastric carcinomas (80 and 88%, respectively) and with biopsies of human mammary and nonsmall-cell lung carcinomas (17,29).…”
mentioning
confidence: 99%